Peak oil paradigm shift : the urgent need for a sustainable energy model - Abdullah, Bilaal (Medianet Ltd. St. JamesTT, 2005)
Refers to the stage of oil production when the level of production can no longer be increased in response to increasing demand and calls on the world community to urgently address the issue of finite and depleting stocks of the plantet's oil.